Ernest Renan and Marcus Aurelius: On the End of the Ancient World - Protopapas-Marneli, Maria (Peitho. Examina Antiqua, 2017)
According to Renan, the day of Marcus Aurelius’ death could be considered as the decisive moment in the downfall of the ancient civilization. He, thus, wonders: “If Marcus Aurelius, the unique emperor-philosopher, did not succeed in saving the world, who else, then, could have saved it?” He notes that the emperor’s death was followed by the succession to the throne of his corrupted son, Commodus, and his friends, who all were all ignorant. Renan observes that the emperor’s kindness could not have prevented the unfortunate fate that befell the Roman Empire after his death. What we have here is the perennial problem, already established in Plato, regarding the role of the philosopher-king in establishing a good state and educating good citizens. However, the case of Marcus Aurelius, as demonstrated by Renan in his book, shows the inability of philosophy to serve the real needs, which ultimately leads to disastrous and irreparable consequences. The present paper attempts to reconstruct the reasons for the unsuccessful application of philosophy, especially the philosophy of the Hellenistic era, to the administrative system of the Roman Empire. It is argued that the failure is mainly due to political, religious and cultural problems.